Geriatric Engineering: An Engineering Systems Design Approach to Human Aging - Lubliner, David J. (Journal of the American Geriatrics Society (JAGS), 2021)
This article explores the development of an interdisciplinary Geriatric Engineering 5‐year Bachelor of Science degree program. The process evolved over 5 years and began with exploring the need, precedents, and data acquisition from target individuals 60 to 92 years of age. The economics of aging necessitates training engineers to design and implement systems that drastically reduce costs. The literature search confirmed the need for medical and engineering collaboration. The precedents for a medical‐engineering curriculum were found to exist in several graduate MD/MS Engineering programs. Finally, data were gathered from several hundred over 60‐year olds, via a research questionnaire and interviews that supported that technology assistance to promote independent living was desired by a significant portion of older individuals. With confirmatory data in hand, geriatric engineering courses were introduced in 2017 at an engineering college. Feedback of more than 100 students who completed these courses was positive. An Advisory Board, composed of medical companies, hospitals, and target population individuals, supported a Geriatrics Engineering minor. The college's undergraduate curriculum committee then established a minor in Geriatric Engineering in 2019, as the next logical step in the process toward developing a bachelor's degree. In conclusion, student feedback from several years of Geriatric Engineering courses, data from individuals over 60 and an advisory board support the next step of creating a Geriatric Engineering Bachelor's degree. Student evaluations/perceptions of the courses were positive. Data and feedback indicate that there is a need for a dedicated undergraduate Geriatric Engineering program. See related editorial by Herr et al. in this issue.